Download presentation

Presentation is loading. Please wait.

Published byMaribel St. john Modified about 1 year ago

1
1.2 – Order of Operations

2
Order of Operations 1.2 – Order of Operations

3
Order of Operations Parentheses 1.2 – Order of Operations

4
Order of Operations Parentheses Exponents 1.2 – Order of Operations

5
Order of Operations Parentheses Exponents Multiplication 1.2 – Order of Operations

6
Order of Operations Parentheses Exponents Multiplication Division 1.2 – Order of Operations

7
Order of Operations Parentheses Exponents Multiplication Division Addition 1.2 – Order of Operations

8
Order of Operations Parentheses Exponents Multiplication Division Addition Subtraction 1.2 – Order of Operations

9
Order of Operations ParenthesesPlease Exponents Multiplication Division Addition Subtraction 1.2 – Order of Operations

10
Order of Operations ParenthesesPlease ExponentsExcuse Multiplication Division Addition Subtraction 1.2 – Order of Operations

11
Order of Operations ParenthesesPlease ExponentsExcuse MultiplicationMy Division Addition Subtraction 1.2 – Order of Operations

12
Order of Operations ParenthesesPlease ExponentsExcuse MultiplicationMy DivisionDear Addition Subtraction 1.2 – Order of Operations

13
Order of Operations ParenthesesPlease ExponentsExcuse MultiplicationMy DivisionDear AdditionAunt Subtraction 1.2 – Order of Operations

14
Order of Operations ParenthesesPlease ExponentsExcuse MultiplicationMy DivisionDear AdditionAunt SubtractionSally 1.2 – Order of Operations

15
Example 1

16
Find the value of [2(10 - 4) 2 + 3] ÷ 5.

17
Example 1 Find the value of [2(10 - 4) 2 + 3] ÷ 5. [2(10 - 4) 2 + 3] ÷ 5 =

18
Example 1 Find the value of [2(10 - 4) 2 + 3] ÷ 5. [2(10 - 4) 2 + 3] ÷ 5 = [2(6) 2 + 3] ÷ 5

19
Example 1 Find the value of [2(10 - 4) 2 + 3] ÷ 5. [2(10 - 4) 2 + 3] ÷ 5 = [2(6) 2 + 3] ÷ 5 [2(36) + 3] ÷ 5

20
Example 1 Find the value of [2(10 - 4) 2 + 3] ÷ 5. [2(10 - 4) 2 + 3] ÷ 5 = [2(6) 2 + 3] ÷ 5 [2(36) + 3] ÷ 5 [72 + 3] ÷ 5

21
Example 1 Find the value of [2(10 - 4) 2 + 3] ÷ 5. [2(10 - 4) 2 + 3] ÷ 5 = [2(6) 2 + 3] ÷ 5 [2(36) + 3] ÷ 5 [72 + 3] ÷ 5 75 ÷ 5

22
Example 1 Find the value of [2(10 - 4) 2 + 3] ÷ 5. [2(10 - 4) 2 + 3] ÷ 5 = [2(6) 2 + 3] ÷ 5 [2(36) + 3] ÷ 5 [72 + 3] ÷ 5 75 ÷ 5 15

23
Example 2

24
Evaluate x 2 – y(x + y) if x = 8 and y = 1.5.

25
Example 2 Evaluate x 2 – y(x + y) if x = 8 and y = 1.5. x 2 – y(x + y) =

26
Example 2 Evaluate x 2 – y(x + y) if x = 8 and y = 1.5. x 2 – y(x + y) = 8 2 – 1.5( )

27
Example 2 Evaluate x 2 – y(x + y) if x = 8 and y = 1.5. x 2 – y(x + y) = 8 2 – 1.5( ) 8 2 – 1.5( )

28
Example 2 Evaluate x 2 – y(x + y) if x = 8 and y = 1.5. x 2 – y(x + y) = 8 2 – 1.5( ) 8 2 – 1.5( ) 8 2 – 1.5(9.5)

29
Example 2 Evaluate x 2 – y(x + y) if x = 8 and y = 1.5. x 2 – y(x + y) = 8 2 – 1.5( ) 8 2 – 1.5( ) 8 2 – 1.5(9.5) 64 – 1.5(9.5)

30
Example 2 Evaluate x 2 – y(x + y) if x = 8 and y = 1.5. x 2 – y(x + y) = 8 2 – 1.5( ) 8 2 – 1.5( ) 8 2 – 1.5(9.5) 64 – 1.5(9.5) 64 – 14.25

31
Example 2 Evaluate x 2 – y(x + y) if x = 8 and y = 1.5. x 2 – y(x + y) = 8 2 – 1.5( ) 8 2 – 1.5( ) 8 2 – 1.5(9.5) 64 – 1.5(9.5) 64 –

32
Example 3

33
Evaluate a 3 + 2bc if a = 2, b = -4, and c = -3. c 2 – 5

34
Example 3 Evaluate a 3 + 2bc if a = 2, b = -4, and c = -3. c 2 – 5 a 3 + 2bc = c 2 – 5

35
Example 3 Evaluate a 3 + 2bc if a = 2, b = -4, and c = -3. c 2 – 5 a 3 + 2bc = (-4)(-3) c 2 – 5

36
Example 3 Evaluate a 3 + 2bc if a = 2, b = -4, and c = -3. c 2 – 5 a 3 + 2bc = (-4)(-3) c 2 – 5 (-3) 2 – 5

37
Example 3 Evaluate a 3 + 2bc if a = 2, b = -4, and c = -3. c 2 – 5 a 3 + 2bc = (-4)(-3) c 2 – 5 (-3) 2 – 5 = 8 + 2(-4)(-3)

38
Example 3 Evaluate a 3 + 2bc if a = 2, b = -4, and c = -3. c 2 – 5 a 3 + 2bc = (-4)(-3) c 2 – 5 (-3) 2 – 5 = 8 + 2(-4)(-3) 9 – 5

39
Example 3 Evaluate a 3 + 2bc if a = 2, b = -4, and c = -3. c 2 – 5 a 3 + 2bc = (-4)(-3) c 2 – 5 (-3) 2 – 5 = 8 + 2(-4)(-3) 9 – 5 = – 5

40
Example 3 Evaluate a 3 + 2bc if a = 2, b = -4, and c = -3. c 2 – 5 a 3 + 2bc = (-4)(-3) c 2 – 5 (-3) 2 – 5 = 8 + 2(-4)(-3) 9 – 5 = – 5 = 32 4

41
Example 3 Evaluate a 3 + 2bc if a = 2, b = -4, and c = -3. c 2 – 5 a 3 + 2bc = (-4)(-3) c 2 – 5 (-3) 2 – 5 = 8 + 2(-4)(-3) 9 – 5 = – 5 = 32 = 8 4

42
Example 4

43
Find the area of the following trapezoid. 16 in. 10 in. 52 in.

44
Example 4 Find the area of the following trapezoid. 16 in. A = ½h(b 1 + b 2 ) 10 in. 52 in.

45
Example 4 Find the area of the following trapezoid. 16 in. A = ½h(b 1 + b 2 ) 10 in. 52 in. A = ½h(b 1 + b 2 )

46
Example 4 Find the area of the following trapezoid. 16 in. A = ½h(b 1 + b 2 ) 10 in. = h 52 in. A = ½h(b 1 + b 2 )

47
Example 4 Find the area of the following trapezoid. 16 in. = b 1 A = ½h(b 1 + b 2 ) 10 in. = h 52 in. A = ½h(b 1 + b 2 )

48
Example 4 Find the area of the following trapezoid. 16 in. = b 1 A = ½h(b 1 + b 2 ) 10 in. = h 52 in. = b 2 A = ½h(b 1 + b 2 )

49
Example 4 Find the area of the following trapezoid. 16 in. A = ½h(b 1 + b 2 ) 10 in. 52 in. A = ½h(b 1 + b 2 ) = ½10( )

50
Example 4 Find the area of the following trapezoid. 16 in. A = ½h(b 1 + b 2 ) 10 in. 52 in. A = ½h(b 1 + b 2 ) = ½10( ) = ½10(68)

51
Example 4 Find the area of the following trapezoid. 16 in. A = ½h(b 1 + b 2 ) 10 in. 52 in. A = ½h(b 1 + b 2 ) = ½10( ) = ½10(68) = 5(68)

52
Example 4 Find the area of the following trapezoid. 16 in. A = ½h(b 1 + b2) 10 in. 52 in. A = ½h(b 1 + b 2 ) = ½10( ) = ½10(68) = 5(68) = 340

Similar presentations

© 2017 SlidePlayer.com Inc.

All rights reserved.

Ads by Google